Purification of DNA/RNA in a Microfluidic Device - Fan, Andy (Methods Mol Biol, 2013)
Often, modern diagnostic techniques require the isolation and purification of nucleic acids directly from patient samples such as blood or stool. Many diagnostic tests are being miniaturized onto micro-sized platforms and integrated into microfluidic devices due to the economies resulting from smaller sample and reagent volumes. Often, these devices perform sample preparation in series with the diagnostic tests. The sample preparation steps are vital in order to purify the desired genetic material from potential inhibitors that can interfere with the outcome of the test. There are various techniques used to selectively capture the nucleic acids while washing away potential contamination (proteins, enzymes, lipids, etc.). Two of the most common forms of selective capture are based on nucleic acid binding to silica surface or on the precipitation of nucleic acids with or without the presence of a carrier species. Each of these methods can be performed in liquid phase or in a solid support such as an extraction column. Here we discuss both methods and address microfluidic applications.